(untitled) (Circe de clásicos y modernos, 2023)
In fragment 44 of On Truth, Antiphon seriously criticizes the law and the Athenian judicial practice as a means that promotes hatred and the commission of injustices. As a result, a large number of scholars consider that he rejects the value of legal institutions. Based on a review of Antiphonʼs thought, this paper aims to analyze the possibility that conflict resolution institutions may be beneficial rather than having a completely negative meaning linked to hatred and injustice.